Remote Neural Stimulation Using Magnetic Nanoparticles - Tay, Andy; Di Carlo, Dino (Current Medicinal Chemistry, 2017)
Neural stimulation provides a means for scientists to investigate brain functions and neurological diseases. There is also mounting interest in using remote stimulation of neuronal circuits for brain-machine interfaces. In this review, we highlight recently developed technologies utilizing magnetic nanoparticles to generate heat or exert mechanical forces for remote control of brain circuits and compare these with conventional (electrical stimulation and drugs) and second-generation (ultrasound and light) techniques. We also present some of the challenges and progress in areas like genetics, nanoparticle synthesis and energy delivery devices to translate the use of these innovative nanoparticle-based platforms in research and clinical settings.
Keywords: TRPV1